A sensitive mitochondrial thermometry 2.0 and the availability of thermogenic capacity of brown adipocyte - Meng, Xiao-Yan; Wang, Dian-Dian; Xie, Tao-Rong; Yang, Run-Zhou; Liu, Chun-Feng; Liu, Dan-Hua; Li, Shu-Ang; Luan, Yi; Kang, Jian-Sheng (Frontiers in Physiology, 2022)
The temperature of a living cell is a crucial parameter for cellular events, such as cell division, gene expressions, enzyme activities and metabolism. We previously developed a quantifiable mitochondrial thermometry 1.0 based on rhodamine B methyl ester (RhB-ME) and rhodamine 800 (Rh800), and deduced the theory for mitochondrial thermogenesis. Given that RhB-ME needs de novo synthesis so that it was not readily available, thus, we further evolved a convenient and sensitive mitochondrial thermometry 2.0 based on tetra-methyl rhodamine methyl ester (TMRM) and Rh800 for the thermogenic study of brown adipocyte. TMRM was demonstrated to be more sensitive (~1.4 times) to temperature than RhB-ME, and thus the TMRM-based mito-thermometry 2.0, which could be easily used for the qualitatively dynamic profiles for mitochondrial temperature and membrane potential in living cells simultaneously. Therefore, TMRM-based mito-thermometry 2.0 was used to measure the availability of thermogenic capacity of brown adipocyte under various stimulations